Hubungan Tingkat Pendidikan dan Pengetahuan Ibu Tentang Gizi dengan Status Gizi pada Balita di Posyandu Abung Timur Wilayah Kerja Puskesmas Bumi Agung Kabupaten Lampung Utara Tahun 2020 - Sutrisno Sutrisno; Huwairits Tamim (Penerbit Goodwood, 2023)
Purpose: The purpose of this study is that there is a relationship between the level of education and knowledge of mothers about nutrition and nutritional status of toddlers at the Abung Timur Posyandu in the working area of the Bumi Agung Community Health Center, North Lampung Regency in 2020. Method: This type of quantitative research with a cross-sectional design, the population in this research were all mothers giving birth with preeclampsia at the Batin Mangunang Regional General Hospital in 2020, with a case sample of 70 patients. The analysis used univariate and bivariate by using Chi Square test. This type of research is quantitative with a cross sectional approach. This population is all mothers who have toddlers with an age range of 2 weeks to 59 months who are in the working area of the Bumi Agung Health Center with a population of 426 children under five and the sample is Simple Random Sampling. The sample of this study was 62 respondents according to predetermined inclusion criteria. Analysis of the data used for variate analysis of the frequency distribution and bivariate analysis using the chi square test. Results: The research, 35 respondents who had less knowledge obtained 32 (91.4%) under nutrition status and as many as 38 respondents who had basic education (SD-SMP) obtained 32 (84.2%) malnutrition status There was a significant relationship between education levels (p-value (0.000)). and maternal knowledge about nutrition (p-value (0,000)). with the nutritional status of children under five at Posyandu Abung Timur, the Working Area of the Bumi Agung Health Center, North Lampung Regency in 2020.